Anxiety and Smoking and Drinking Behaviors among Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study aimed to investigated the anxiety and smoking and drinking behaviors of adolescents in one region of South Korea. This was a secondary data analysis study using data from a survey on youth smoking and drinking. This study found that the distribution of mild, moderate, and severe anxiety levels was higher among smokers than among nonsmokers (χ2 = 15.343, p<0.001). In addition, the distribution of mild, moderate, and severe anxiety levels was higher among drinkers than among nondrinkers (χ2 = 195.305, p<0.001). It is necessary to prevent mental disorders related to anxiety symptoms through smoking and drinking prevention programs for adolescents in a community.